Represented speech as a rhetorical device in 10+ nights - Nguyen, Thi Thu Thuy (H. : ĐHQGHN, 2018)
Represented speech has long been a subject of research in linguistics and literary criticism from a variety of perspectives. From a stylistic one, we conduct this study of represented speech in narratives with data from the novel 10+ nights by Hồ Anh Thái so as to clarify I.R. Galperin’s view (1971) which posits that represented speech is a rhetorical device. The paper clarifes the following issues: (i) What is a rhetorical represented speech?, (ii) Is all represented speech in literary works a rhetorical device?, and (iii) If not, what are unique characteristics of rhetorical represented speech? The major methods used in this study include: classifcation (classifying types of represented speech), description (describing types, patterns and linguistic features of represented speech), and rhetorical analysis (analyzing rhetorical values and impact of represented speech so as to generalize theoretical arguments). The data used for this study include direct represented speech that does not conform to regular rules. This paper starts with concepts of represented speech as a rhetorical device, followed by rhetoric represented speech in 10+ nights and ways to identify rhetoric represented speech in 10+ nights before the conclusion